Acute Minocycline Treatment Mitigates the Symptoms of Mild Blast-Induced Traumatic Brain Injury - Kovesdi, Erzsebet; Kamnaksh, Alaa; Wingo, Daniel; Ahmed, Farid; Grunberg, Neil E.; Long, Joseph B.; Kasper, Christine E.; Agoston, Denes V. (Frontiers in Neurology, 2012)
Mild traumatic brain injury (mTBI) represents a significant challenge for the civilian and military health care systems due to its high prevalence and overall complexity. Our earlier works showed evidence of neuroinflammation, a late onset of neurobehavioral changes, and lasting memory impairment in a rat model of mild blast-induced TBI (mbTBI). The aim of our present study was to determine whether acute treatment with the non-steroidal anti-inflammatory drug minocycline (Minocin®) can mitigate the neurobehavioral abnormalities associated with mbTBI, Furthermore, we aimed to assess the effects of the treatment on select inflammatory, vascular, neuronal, and glial markers in sera and in brain regions associated with anxiety and memory (amygdala, prefrontal cortex, ventral, and dorsal hippocampus) following the termination (51 days post-injury) of the experiment. Four hours after a single exposure to mild blast overpressure or sham conditions, we treated animals with a daily dose of minocycline (50 mg/kg) or physiological saline (vehicle) for four consecutive days. At 8 and 45 days post-injury, we tested animals for locomotion, anxiety, and spatial memory. Injured animals exhibited significantly impaired memory and increased anxiety especially at the later testing time point. Conversely, injured and minocycline treated rats’ performance was practically identical to control (sham) animals in the open field, elevated plus maze, and Barnes maze. Protein analyses of sera and brain regions showed significantly elevated levels of all of the measured biomarkers (except VEGF) in injured and untreated rats. Importantly, minocycline treatment normalized serum and tissue levels of the majority of the selected inflammatory, vascular, neuronal, and glial markers. In summary, acute minocycline treatment appears to prevent the development of neurobehavioral abnormalities likely through mitigating the molecular pathologies of the injury in an experimental model of mbTBI.